PENINGKATAN MOTIVASI BELAJAR MAHASISWA TERHADAP PRESTASI BELAJAR ALJABAR MATRIKS - Nita Hidayati (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The objectives of this research is examine the impact of learning motivation of students in algebra matrix. Data collection techniques used in this study is the observation, questionnaires, tests, and documentation. The population in this study is a second semester student of Mathematics Education in UNSIKA Karawang. This research used purposive sampling techniques that have one class into the sample. In this study the researchers used one shot case study design. It is the result of observation after treatment. Indicators and variables that measured is learning achievement that includes the value of the midterm as the independent variable and final exams as the dependent variable. Data analysis is using Wilcoxon signed rank test. In the Wilcoxon signed rank test (, n,) showed that the learning motivation significantly increasing the value of UTS and UAS. The value of Means there is an increased motivation to learn students from UTS to UAS. This shows that the impact is positive motivation to learn. Therefore, the motivation has positive benefits for increase the value of UTS and UAS college students.